The Role of Images in the Translation of Technical and Scientific Texts - Tercedor-Sánchez, María; Abadía-Molina, Francisco (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe information transmitted by images accompanying technical and scientific texts id supposed to lead to a better, visually-oriented understanding of the concepts and descriptions contained in the text. Given that conceptualising scientific information entails creating mental representations of the concepts, and since the function of images is complementary to the function of texts, cultural attitudes might well influence many aspects of an image ranging from its contents, to shape or colour. One might ask if the translation process should include the adaptation of original images in the text in order to avoid a misunderstanding of the message by readers from a target culture, or if images should be treated differently depending on the target audience.As images in technical and scientific books and articles are often difficult to interpret a close study of them is needed so that the visual message matches the knowledge of the receiver in the target culture. In this article we propose cognitive and pragmatic criteria regarding the message transmitted by images in scientific texts as a guide to translation-oriented image analysis.